Go with your gut: microbiota meet microglia - Mosher, Kira Irving (Nat Neurosci, 2015)
Discovering the environmental factors that control microglia is key to understanding and managing brain health. A new study finds that microbiota in the gut are essential for regulating microglia maturation and activation.